Induction of regulatory T cells and dominant tolerance by dendritic cells incapable of full activation. - Yates, S; Paterson, A; Nolan, K; Cobbold, S; Saunders, N; Waldmann, H; Fairchild, P (2007)
Transplants tolerated through a process known as infectious tolerance evoke continuous recruitment of regulatory T (Treg) cells that are necessary to maintain the unresponsive state. This state is maintained long-term and requires continuous Ag exposure. It is not known, however, whether infectious tolerance operates through sustained recruitment of pre-existing regulatory cells, induction of regulatory cells, or both. Using mice deficient in natural Treg cells, we show here that quiescent donor dendritic cells (DC) laden with histocompatibility Ag can induce Treg cells de novo that mediate transplantation tolerance. In contrast, fully activated DC fail to do so. These findings suggest that DC incapable of delivering full activation signals to naive T cells may favor their polarization toward a regulatory phenotype. Furthermore, they suggest a role for quiescent endogenous DC in the maintenance of the tolerant state.